Optimalisasi Peluang Media Digital: Strategi Meningkatkan Fundraising Zakat di Lembaga Taman Zakat Indonesia - Ghosyi Harfiah Ningrum; Reza Dwi Firnanda; Widya Purnamasari; Bakhrul Huda (Universitas Islam Negeri Sunan Ampel Sunan Ampel, 2021)
Indonesia as a country with a majority Muslim population, daily life cannot be separated from the influence of Islam. One of the teachings of Islam that contains the meaning of the balance of the hereafter is zakat. Zakat is also one of the drivers of the Indonesian economy. Outlook Zakat 2017, states that every year the national zakat collection reaches 30.55%. However, the collection in the field only reached 5 trillion. This illustrates the high enthusiasm of the government and society in raising funds, but the efforts made are less than optimal. Coupled with increasingly modern technology, it will be able to support activities to be more effective and efficient, especially in collecting zakat funds. Using descriptive qualitative methods, researchers want to examine more deeply related to (1) the pattern used in the use of digital media, then identify (2) the opportunities and risks that arise from the use of digital media, so that it can be seen (3) the digital fundraising management strategy formulated in order to achieve the optimal level by LAZ Taman Zakat Indonesia. Primary data in the form of information obtained from primary sources through moderate participation observation activities and unstructured interview techniques. Meanwhile, secondary data is in the form of planning documents and activity reports obtained through documentation activities. With data analysis techniques of data reduction, data presentation, and drawing conclusions. As a result, the pattern of using digital media by LAZ Taman Zakat Indonesia in the activities of collecting zakat funds has been systematically designed. Coupled with the identification process of the opportunities and risks of using digital media. So that it has described the digital fundraising management strategy of zakat by LAZ Taman Zakat Indonesia to reach the optimal level.